Pengaruh Pemberian Limbah Tepung Roti Afkir Dalam Ransum Terhadap Recahan Karkas Ayam Kampung - I Gusti Agung Putra Narayana I gusti agung putra narayana; Ni Ketut Sri Rukmini; Ni Ketut Etty Suwitari (Fakultas Pertanian, Universitas Warmadewa, 2022)
The purpose of this study was to determine the effect of replacing corn with discarded bread flour on carcass crumbs of super free-range chicken during a 10-week rearing period and the level of use of rejected bread flour in what percentage will have an effect on carcass crumbs of super free-range chicken aged 10 weeks. The design used was a completely randomized design (CRD) with 5 (five) treatments and 3 (three) replications so that there were 15 cage units and each unit consisted of 5 free-range chickens and 75 free-range chickens were used. The treatments were as follows: rations without Bread Flour (TRA) (P0), rations containing 10% TRA (P1), rations containing 20% ​​TRA (P2), rations containing 30% TRA (P3) and rations containing 40% TRA (P4 ). The results showed that the replacement of corn with rejected bread flour had a significant (P<0.05) to very significant (P<0.01) effect on breast weight, wing weight, thigh weight, and back weight of super free-range chickens during the 10-month rearing period. week. The level of use of the best rejected bread flour is 20% with the weight of the chest, thighs, wings and back of 113.70 g/head, 154.30 g/head, 63.43 g/head and 101.13 g/head, respectively